(untitled) (El-Wahat Journal for Research and Studies, 2020)
Algerian popular poetry is a rich heritage that can be exploited by researchers from the various disciplines of the human and social sciences. The work of collecting and transcribing is the first step towards discovering thes documents. For that reason, the French who were in Algeria during the French colonization, devoted themselves to collecting and translating this poetry in the different regions of the country, taking into account the documentary value it offers. The African journal counts among its articles a big number of popular poems published by collaborators that responded to the mission of scientific exploration of the colonized country. In this article, we propose to study the texts translated into French of Algerian popular poetry published in the African journal, analysing the themes they develop, according to the genre of the poem. Through this thematic reading, we will analyze the expression of the colonized Algerian: his identity, his condition of colonized, his revolt as well as his daily life. As for the expression of the colonizer, it is revealed in the choice of published texts. KEYWORDS: The African Journal – Colonized – Algerian popular poetry – thematic approach